Exclusive Breastfeeding and Decrease of Upper respiratory Infection Incidence among Infants Aged 6-12 Months in Kampar District, Riau Province - Rustam, Musfardi; Mahkota, Renti; Kodim, Nasrin (UI Scholars Hub, 2019)
Upper Respiratory Infection (URI) is a major cause of morbidity and mortality of infants and toddlers in developing countries. The high infant morbidity and mortality rates in Indonesia are associated with the low exclusive breastfeeding ability. Breast milk is a natural drink for newborns in the first month of life that is beneficial not only for the babies, but also for mothers. The aim of study was to determine exclusive breastfeeding and decrease in incidence of URI among infants aged 6-12 months. This study was conducted by using case control design. Samples were taken by using cluster random sampling. Subject of study consisted of 162 cases and 162 control with infants aged 6-12 years. Cases were 162 infants aged 6-12 months suffering from URI within one last month and taken by mothers to primary health care that was selected location of study, while control was mothers who took their infants aged 6-12 months who did not suffer from URI within one last month to the selected primary health care. Data analysis included univariate, bivariate, stratification, and multivariate analysis with logistic regression. Results of study found that infants who were not exclusively breastfed were 1.69 times (95% CI: 1.02-2.80) more at risk of increasing URI incidence compared to infants who were breastfed exclusively after controlled by smoker in house and immunization variables. Health promotion of 6-month exclusive breastfeeding, provision of immunization, and anti-smoking program need to be implemented continuously to decrease the rates of morbidity and mortality due to URI disease.